Hilary Lipka – Bruce Wells (eds.), Sexuality and Law in the Torah (Library of Hebrew Bible/Old Testament Studies 675; London: Clark 2020). - Majewski, Marcin (The Biblical Annals, 2021)
Book Review: Hilary Lipka – Bruce Wells (eds.), Sexuality and Law in the Torah (Library of Hebrew Bible/Old Testament Studies 675; London: Clark 2020).